Revision surgery after trapeziometacarpal arthroplasty - Megerle, Kai Oliver; Grouls, Stephan; Germann, Günter; Kloeters, Oliver; Hellmich, Susanne (Archives of orthopaedic and trauma surgery, 2011)
Background: The majority of patients with trapeziometacarpal joint (TMJ) arthritis can be successfully treated with some form of arthroplasty. Residual pain therefore is rather uncommon, but particularly difficult to treat. The aims of this study were to determine the number of patients in need of additional surgery; to identify the most common causes for persistent pain and to establish a treatment algorithm. Patients: Twelve patients (11 females, 1 male) who had undergone secondary surgery after TMJ arthroplasty were retrospectively analyzed at a mean time of 32 months after the primary procedure. Parameters included the indication for secondary surgery, the type of procedure, the ultimate range of motion, residual pain levels, upper extremity function assessed by the DASH score and the distance from the first metacarpal bone to the scaphoid. Results: The overall results were assessed according to the Conolly score. The revision rate after primary arthroplasty at our institution was 2.9%. Most common problems for secondary surgery included mechanical pain due to crepitation of the base of the first metacarpal bone, neuropathy of the superficial branch of the radial nerve and concomitant scaphotrapezial arthritis. A total of 19 procedures were performed resulting in two good, five fair and five poor results. A treatment algorithm is presented.